Laparoscopic Roux-en-Y cystojejunostomy with indocyanine green angiography for a recurrent large pancreatic pseudocyst: a case report - Dashputra, Amit V.; Sachin S., Sholapur; Amol N., Wagh; Shirish R., Bhagvat (International Surgery Journal, 2024)
Symptomatic pseudocyst of pancreas can present as abdominal pain or back pain, early satiety, unexplained weight loss, jaundice, steatorrhea, or a palpable mass. This case involves a 31-year-old male with a large, recurrent pseudocyst, initially managed by endoscopic drainage, then complicated by recurrence. Despite failed attempts at a repeat endoscopic cystogastrostomy, surgical intervention was successful, albeit challenging due to the patient’s physique and cyst size. Roux-en-Y cystojejunostomy was performed, aided by intravenous indocyanine green (ICG) angiography to ensure anastomotic vascularity. Postoperative recovery was smooth, and the patient was asymptomatic after 4 months without residual collections. Thoughtful intervention is vital for managing such pseudocysts, with surgical drainage remaining crucial, albeit with adaptable port placement. Choice between cystogastrostomy and cystojejunostomy should consider pseudocyst location for optimal drainage. The use of indocyanine green angiography for assessing vascularity supports the success of anastomosis intra-operatively and presents an intriguing research avenue.